Distance education features using Facebook - Dhyab, Rozhgar; Varol, Asaf (International Association of Online Engineering, 2018)
Thanks to rapid development of information technology there are many new tools that can be used for teaching and learning environment. In the long past, we had met classical classrooms where teachers had to use chalk to write done everything on the blackboard. Later, we have met new tools such as projection, desktop computers, smart boards, etc. in the classical classrooms. Nowadays, we have met with mobile devices. Mobile devices are magic tools which can be used for teaching and learning as a distance. Because of its mobility we do not need to join a classical classroom to listen to courses offered by our teachers any more. Now, we can join in virtual classroom which can be established on cloud. On the other hand, there are many social media applications which can be also used for teaching and learning. For example, it is now possible to teach courses by online where Facebook can be used as a supplementary tool. There are instructors who use Facebook as a learning environment where instructors and learners interact simultaneity on it. The Facebook has made a significant contribution towards solving the problems faced by practical education students during the period of practical education. There is an increasing trend in the study community to use Facebook in order to solve these problems. The aim of this research is to encourage instructors and students to teach and learn by using Facebook as part of a new system of education, namely online distance learning. In this study we explain how mobile devices and social media have been used during teaching and learning of courses at master studies' level at the Department of Software Engineering of College of Technology at Firat University in Turkey. We will explore the advantages and disadvantages of Facebook in terms of teaching and learning environment and we will suggest some recommendations for using Facebook as a teaching and learning platform which have been resulted from our research. © 2018, International Association of Online Engineering.
Keywords: Communication; E-learning; Education; Facebook; Learning management system (LMS); Social networks; Web 2.0